THE RESPONSE OF SPRING BARLEY VARIETIES ON THE PRE-SOWING TREATMENT OF SEEDS - N. G. Chertkova; Yu. G. Skvortsova; T. I. Firsova (Зерновое хозяйство России)
The modern technologies of any crop growing, including barley, include seed disinfection with the fungicides as an obligatory agro method, because the sowing properties of the seeds greatly affect on the formation of large and stable yields. The use of the growth stimulator is substantiated with a large range of their effect on the plants, a possibility to regulate some stages of development to increase the yield of the product. The article considers the results of the trials and the effect of the disinfectant ‘Vintsit Forte’ and the mixture of the disinfectant with the growth stimulators ‘Fertigrein Start’ and ‘Fundazol’ on the productivity and seed quality of the heat and dry tolerant varieties of spring barley ‘Leon’ and ‘Shchedry’. The use of the mixture of the fungicide ‘Vintsit Forte’ and the growth stimulator positively influences on the formation of such structural element of the yield, as a productive tillering. The largest increase of spring barley productivity has been obtained in the variants of the mixture of the disinfectant ‘Vintsit Forte’ and the growth stimulator ‘Fertigrein Start’. The variety ‘Leon’ gave the productivity increase of 1.4 t/ha (41.2%) in comparison with the control; the vaiety ‘Shchedry’ – 2.3 t/ha(62.1%). In the variants of separate treatment with ‘Vintsit Forte’, ‘Fertigrein Start’ and ‘Fundazol’ the productivity slightly increased. The largest indexes of all qualitative traits (length of head, number of kernels per head, weight of kernels per head, 1000-kernel weight) have been received due to the seed treatment with ‘Vintsit Forte’+‘Fertigrein Start’. The article has considered an economic efficiency of pre- sowing treatment of seeds. The largest profitability of the varieties ‘Shchedry’ (197.6%) and ‘Leon’ (138.1%) has been obtained after the seed treatment with the mixture of the disinfectant and the growth stimulator.